Evaluation of Four Vertical Jump Tests: Methodology, Reliability, Validity, and Accuracy - Aragón Vargas, Luis Fernando (2000)
Vertical jump performance tests can give considerably different results, even when different methods are used to analyze the same jump trial from the same subject. To evaluate and compare 4 different methods commonly used to measure vertical jump performance, 52 physically active men each performed 5 maximal vertical jumps. Kinetic and kinematic data were used to analyze each trial using the 4 methods: a criterion test based on body center of mass displacement (VJPT), 2 methods based on vertical takeoff velocity as calculated from the force platform, and 1 method based on time in the air (JUMPAIR). All 4 methods showed excellent reliability (R > .97). Using VJPT as the criterion, the other 3 methods showed excellent coefficients of validity (R > .95) but poor accuracy: The obtained vertical jump height scores were statistically different among all methods (p < .01). JUMPAIR is considered a relatively simple and inexpensive method to obtain valid and reliable measures of vertical jump performance without an arm swing, provided the appropriate adjustments are made to the jump results.